usando a multiplicação , calcule
a) (1+√5)²
b) (2-√3)²
c) (√5+√3)²
d) (√7-√2)²
agradeço quem puder ajuda
Respostas
respondido por:
24
(1 + √5)² = (1 +√5) . (1 + √5) = 1 + √5 + √5 + 5 = 6 + 2√5 ou 2(3 +√5)
(2 - √3)² = (2 - √3) . ( 2 - √3) = 4 - 2√3 - 2√3 + 3 = 7 - 4√3
(√5 + √3)² = (√5 + √3). (√5 +√3) = 5 + √15 + √15 + 3 = 8 + 2√15 ou 2(4 + √15)
(√7 - √2)² = (√7 - √2).(√7 - √2) = 7 - √14 - √14 + 2 = 9 - 2√14
(2 - √3)² = (2 - √3) . ( 2 - √3) = 4 - 2√3 - 2√3 + 3 = 7 - 4√3
(√5 + √3)² = (√5 + √3). (√5 +√3) = 5 + √15 + √15 + 3 = 8 + 2√15 ou 2(4 + √15)
(√7 - √2)² = (√7 - √2).(√7 - √2) = 7 - √14 - √14 + 2 = 9 - 2√14
Anônimo:
a) 6+2√5
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás